2012
DOI: 10.1007/s10461-012-0239-5
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Behavior as a Function of Stigma and Coping with Stigma Among People with HIV/AIDS in Rural New England

Abstract: The relationship between coping with HIV/AIDS stigma and engaging in risky sexual behavior (i.e., inconsistent condom use) was examined in HIV-positive adults living in rural areas. Participants answered questions about their experiences with HIV/AIDS prejudice and discrimination (enacted stigma) and their perceptions of felt HIV/AIDS stigma (disclosure concerns, negative self-image, and concern with public attitudes). They were also asked about how they coped with HIV/AIDS stigma, and about their sexual activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 62 publications
0
36
0
Order By: Relevance
“…This suggests that disclosure of HIV status to a partner may be important to get support from family or partners. Some research has found that increased HIV/AIDS stigma directly or indirectly predicted unsafe sexual behaviour [25]- [27] and people who perceived more HIV related stigma were less likely to disclose their HIV status to partners [28].…”
Section: 00mentioning
confidence: 99%
“…This suggests that disclosure of HIV status to a partner may be important to get support from family or partners. Some research has found that increased HIV/AIDS stigma directly or indirectly predicted unsafe sexual behaviour [25]- [27] and people who perceived more HIV related stigma were less likely to disclose their HIV status to partners [28].…”
Section: 00mentioning
confidence: 99%
“…Moreover, there is some evidence indicating that abstinent individuals are psychologically distressed in much the same way as are individuals who engage in risky sex (Varni, Miller, & Solomon, 2012). Abstinence, especially abstinence arising from lack of opportunity, is associated with psychological symptoms such as depressed mood (Donnelly, Burgess, Anderson, Davis, & Dillard, 2001; Wagner, Rabkin, & Rabkin, 1993), anger, and frustration (Donnelly, et al, 2001).…”
mentioning
confidence: 99%
“…There was a great amount of internalized stigma in this study, which could be a prime reason for the nondisclosure of the participants, as suggested by Tsai et al 24 Since most of the individuals used avoidance as a coping mechanism, it could lead to a greater negative psychological impact. 11,12 The social rejection faced by the participants in this study was in the form of not sharing food, water, or room. Such mentality existing in the HIV-free population was highlighted by others as well.…”
Section: Discussionmentioning
confidence: 99%
“…8 Stigma is a major barrier for the successful treatment of the PLWHA worldwide as highlighted by a number of studies. [9][10][11][12][13][14][15][16][17][18] We report the first study related to stigma in the North Karnataka Region of India, which is one of the most underdeveloped areas of the state and has a high prevalence of HIV/AIDS.…”
Section: 5005/jp-journals-10024-2123mentioning
confidence: 98%